2021
DOI: 10.3389/fpsyg.2021.621094
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mindset and College Students’ Learning Engagement During the COVID-19 Pandemic: A Serial Mediation Model

Abstract: Against the scourge of the COVID-19 pandemic, college students’ learning engagement has become a key issue in universities and society. Guided by the theories of existential positive psychology and social perception, we explored the positive effect of a growth mindset on learning engagement during the COVID-19 pandemic. A total of 1,040 college students from universities in Henan Province of China effectively completed online questionnaires. The results showed that growth mindset was positively related to lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 60 publications
(67 reference statements)
3
46
0
2
Order By: Relevance
“…Our findings are consistent with some previous studies. Specifically , Zhu et al (2021) found that the daily number of code blue events in the COVID-19 pandemic context was positively correlated with nurses' daily occupational calling, and COVID-19 pandemic strength positively predicted perceived stress (Zhao et al, 2021), which resulted in job burnout (Yıldırım & Solmaz, 2020) and fatigue (Zhou et al, 2020). These findings enrich the empirical research base of EST and highlight the important influence of COVID-19 pandemic criticality on workplace outcomes among Chinese police officers.…”
Section: Theoretical Implicationsmentioning
confidence: 76%
“…Our findings are consistent with some previous studies. Specifically , Zhu et al (2021) found that the daily number of code blue events in the COVID-19 pandemic context was positively correlated with nurses' daily occupational calling, and COVID-19 pandemic strength positively predicted perceived stress (Zhao et al, 2021), which resulted in job burnout (Yıldırım & Solmaz, 2020) and fatigue (Zhou et al, 2020). These findings enrich the empirical research base of EST and highlight the important influence of COVID-19 pandemic criticality on workplace outcomes among Chinese police officers.…”
Section: Theoretical Implicationsmentioning
confidence: 76%
“…Academic engagement is described as “learners’ psychological effort and investment toward learning, understanding, or mastering the skills, crafts, or knowledge that the coursework is intended to promote” ( Lamborn et al, 1992 , p. 13). Learners’ academic engagement includes individual and contextual features that interact with each other to demonstrate their positive attitudes toward learning ( Zhao et al, 2021 ). Eccles (2016) argued that learner academic engagement has a positive and significant relationship with academic achievement and resilience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growth mindset has been widely researched able to have a positive impact on the problems encountered in the field of education, such as helping to overcome some psychological barriers (Duchi et al, 2020), even being able to cope with issues that arise from events COVID-19 today (Zhao et al, 2021). In addition, other studies said that the growth mindset could improve school wellbeing (Wahidah & Royanto, 2019), learning engagement (Zhao et al, 2021), as well as being able to make the students survive and take action in the face of decline (Bai et al, 2021). Dweck (2006) said that students with a growth mindset believe that getting an optimal result requires hard work and effort.…”
Section: Introductionmentioning
confidence: 99%